2023
DOI: 10.1063/5.0137931
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed high stability top-gate W and F co-doped ZnSnO thin film transistors

Abstract: In this work, top-gate structured W: F co-doped Zn–Sn–O (ZTO) thin-film transistors (TFTs) with excellent stability are prepared by the solution process. Comparing with the undoped ZTO TFT, the mobility of W: F co-doped ZTO TFTs was up from 1.87 to 3.14 cm2 V−1 s−1, and the subthreshold swing decreases from 0.192 to 0.157 V/dec. Moreover, the W: F co-doped ZTO TFTs exhibit a small Vth shift of −0.09 V under negative bias illumination stress, which is close to one of the TFTs prepared by the traditional vacuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…15 Recently, codoping has been proposed as an effective strategy to promote TFT performance, exhibiting an advantage over single doping. 16 Hu et al reported W and F codoped ZnSnO TFTs, achieving a mobility of 3.14 cm 2 /V•s and excellent negative bias illumination stress stability. 16 Hong et al fabricated Si and N codoped ZnO TFTs by atomic layer deposition.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Recently, codoping has been proposed as an effective strategy to promote TFT performance, exhibiting an advantage over single doping. 16 Hu et al reported W and F codoped ZnSnO TFTs, achieving a mobility of 3.14 cm 2 /V•s and excellent negative bias illumination stress stability. 16 Hong et al fabricated Si and N codoped ZnO TFTs by atomic layer deposition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 Hu et al reported W and F codoped ZnSnO TFTs, achieving a mobility of 3.14 cm 2 /V•s and excellent negative bias illumination stress stability. 16 Hong et al fabricated Si and N codoped ZnO TFTs by atomic layer deposition. Their study demonstrated the feasibility of carrier concentration modulation through cation and anion codoping.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Solution-processed zinc-tin-oxide (ZnSnO) TFTs were widely investigated due to their excellent properties, such as a low-temperature synthesis process, simple fabrication, low cost, and resource sustainable ability [9][10][11]. However, oxygen vacancies have some negative effects on oxide films.…”
Section: Introductionmentioning
confidence: 99%